Increased Non-Gaussianity of Heart Rate Variability Predicts Cardiac Mortality after an Acute Myocardial Infarction - Hayano, Junichiro; Kiyono, Ken; Struzik, Zbigniew R.; Yamamoto, Yoshiharu; Watanabe, Eiichi; Stein, Phyllis K.; Watkins, Lana L.; Blumenthal, James A.; Carney, Robert M. (Frontiers in Physiology, 2011)
Non-Gaussianity index (λ) is a new index of heart rate variability (HRV) that characterizes increased probability of the large heart rate deviations from its trend. A previous study has reported that increased λ is an independent mortality predictor among patients with chronic heart failure. The present study examined predictive value of λ in patients after acute myocardial infarction (AMI). Among 670 post-AMI patients, we performed 24-hr Holter monitoring to assess λ and other HRV predictors, including standard deviation of normal-to-normal interval, very-low frequency power, scaling exponent α1 of detrended fluctuation analysis, deceleration capacity, and heart rate turbulence (HRT). At baseline, λ was not correlated substantially with other HRV indices (|r| <0.4 with either indices) and was decreased in patients taking β-blockers (P = 0.04). During a median follow up period of 25 months, 45 (6.7%) patients died (32 cardiac and 13 non-cardiac) and 39 recurrent nonfatal AMI occurred among survivors. While all of these HRV indices but λ were significant predictors of both cardiac and non-cardiac deaths, increased λ predicted exclusively cardiac death (RR [95% CI], 1.6 [1.3-2.0] per 1 SD increment, P <0.0001). The predictive power of increased λ was significant even after adjustments for clinical risk factors, such as age, diabetes, left ventricular function, renal function, prior AMI, heart failure, and stroke, Killip class, and treatment ([95% CI], 1.4 [1.1-2.0] per 1 SD increment, P = 0.01). The prognostic power of increased λ for cardiac death was also independent of all other HRV indices and the combination of increased λ and abnormal HRT provided the best predictive model for cardiac death. Neither λ nor other HRV indices was an independent predictor of AMI recurrence. Among post-AMI patients, increased λ is associated exclusively with increased cardiac mortality risk and its predictive power is independent of clinical risk factors and of other HRV predictors.